Cover Crop Development Related to Nitrate Uptake and Cumulative Temperature. Issue 2 (16th February 2017) - Burger, Martin; Dumlao, Matthew R.; Wang, Juan; Moradi, Barzin A.; Horwath, William R.; Silk, Wendy K.
Abstract : Cover crops have been shown to deplete soil nitrate and reduce nitrate leaching in Mediterranean climates. Cover crop canopy development, N uptake, and root system development were studied during three rainy seasons in Yolo silt loam and Rincon silty clay loam soils, with two cover crops with contrasting root systems and N acquisition strategies: triticale (× Triticosecale ), a monocot wheat ( Triticum aestivum L.)–rye ( Secale cereale L.) hybrid with a fibrous root system, and bell bean ( Vicia faba L.), a taprooted legume that fixes N. Weed growth was substantial in bell bean plots. Triticale consistently developed a uniform stand and produced a deeper and denser root system with a faster root penetration rate than the bell bean–weed mixture. Growth and N uptake were strongly correlated with accumulated temperature for triticale but not bell bean. Therefore, triticale growth models based on weather data (1982–2014) were used to study the effect of planting and termination dates on N uptake in Davis, CA. Planting before mid‐October would enable N extraction from the soil prior to the heaviest winter rains, whereas delaying sowing until mid‐November would delay significant N uptake until early spring. Following the current cover crop management approach of sowing triticale before the first significant rain and terminating by the end of February, N uptake from the soil would exceed 45 kg N ha ‐1 ∼56% of the time. Generally, a temperature‐based growth model is useful for managing soil nitrate levels with some monocot cover crops during the winter rainy season.